2018
DOI: 10.1590/1980-5373-mr-2017-0987
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical and Thermal Characterizations of PVA/MAA:EA Polyblend Films

Abstract: Films of polyvinyl alcohol (PVA), Methacrylic Acid -Ethyl Acrylate (MAA:EA) copolymer and their blends PVA:MAA:EA of composition 80:20, 60:40, 50:50, 40:60, 20:80 (wt %) were prepared by using the solution cast technique. The prepared films were investigated by structural, optical and thermal studies. X-ray diffraction (XRD) scans revealed the semicrystalline nature of the blends for lower concentrations of PVA up to 60 wt % and the amorphous nature for higher ones. Fourier transform infra-red spectroscopy (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…The T g of PVA is 96°C, and this is consistent with the previously reported results (it was recorded at 96.3°C) ( [21] cited in [22]), and it shifted after the addition of bentonite to 95°C for PVA/NaB with a clear peak and to approximately 94°C with a weak peak of PVA/SB, whereas the peak of T g was not observed in the DSC curve of PVA/SB2. Strawhecker and Manias [23] reported that "the fully intercalated PVA hybrids [i.e.…”
Section: Analysis Of Thermal and Flammability Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…The T g of PVA is 96°C, and this is consistent with the previously reported results (it was recorded at 96.3°C) ( [21] cited in [22]), and it shifted after the addition of bentonite to 95°C for PVA/NaB with a clear peak and to approximately 94°C with a weak peak of PVA/SB, whereas the peak of T g was not observed in the DSC curve of PVA/SB2. Strawhecker and Manias [23] reported that "the fully intercalated PVA hybrids [i.e.…”
Section: Analysis Of Thermal and Flammability Propertiessupporting
confidence: 92%
“…The second stage can be attributed to the decomposition of the side chain (-OH) of PVA [12,22], and the weight loss was about 75% with a strong peak in the DrTG curve. On the other hand, the third stage can be attributed to the decomposition of the main chain (C-C backbone) of PVA [12,22], and the weight loss was about 15%. The nanocomposite samples showed higher onset temperatures (by 10-20°C) for both the second and third stages, as shown in Table 3.…”
Section: Analysis Of Thermal and Flammability Propertiesmentioning
confidence: 99%
“…Pure PVA has an absorption edge value of around 6.26 eV, while the organocopper-containing samples reveal a wide shift to lower photon energy. Siddaiah et al [62] reported that the value of absorption edge for pure PVA lies at 5.94. The absorption edge value of the current study for pure PVA corresponds to that attained in the study of Siddaiah et al The wide shifting of the absorption edge can be attributed to the distribution and complexation between organocopper and PVA matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern is characteristic of an amorphous phase with the main halo of the typical peak at 2θ of 17.7° and another low intensity peak at 2θ of 20.2°. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%